Familial Factors Influencing Creativity Among Married Employees of Financial Technology Organisations in Lagos - Balogun, Shyngle K.; Attah, Thomas; Famakinde, Oluwafemi P. (Advances in Social Sciences Research Journal, 2021)
Creativity in the workplace is absolutely essential, especially in a financial technology organization in today’s global society. A detailed literature review reveals unclear connection of creativity with some family-related variables among married employees. This study is a further exploration to establish the role of familial factors such as commitment to marriage, marital satisfaction, religiosity and familism in the creativity of FINTECH employees in Lagos, Nigeria. The research was a cross-sectional survey of married employees within FINTECH organizations in Lagos. 224 married employees (135 are males) were conveniently sampled to respond to a structured questionnaire of six sections made up of validated scales that measured constructs of marital commitment, marital satisfaction, religiosity, familism and creativity. Three hypotheses were tested using Pearson product moment correlation, multiple regression analysis and t-test for independent samples at pα.05. Creativity for FINTECH employees has a significant positive relationship with marital commitment (r=.468, p<.01), marital satisfaction (r=.224, p<.01), religiosity (r=.328, p<.01) and familism (r=.452, p<.01). Psychological factors (commitment to marriage, familism, marital satisfaction and religiosity) have a significant joint influence on employee creativity (F (4, 223) = 24.766, p <.01; R2 = .295) and a significant independent contribution of commitment to marriage and familism to employee creativity [(β = .358, p <.01); (β = .287, p <.01) respectively]. There are no significant gender differences in employee creativity (t (217) = 1.656, p > .05). This confirms the hypothesized heightened relationship of familial factors with creativity of employees, especially FINTECH employees. This study rather brings a new suggestion that organizations should not just focus on the conditions of work at the office, or the pay of their employees only, but also give attention to the state of the family of their employees as this influences their abilities to deliver innovative ideas and lofty solutions to nutty problems within the work environment.